Alanine aminotransferase controls seed dormancy in barley - Kazuhiro Sato (Nature Portfolio, 2016)
Seed dormancy allows wild barley grains to survive dry summers in the Near East but has been selected against for industrial applications such as beer and whisky production that require quicker germination. Here Sato et al. show that Qsd1is a major seed dormancy gene in barley and encodes an alanine aminotransferase.